Lateral variations in plagioclase compositions, Main Zone, Bushveld Complex, South Africa: Evidence for slow mixing of magmas in basinal structures. (2nd January 2018) - Cawthorn, R. G.; Lundgaard, K. L.; Tegner, C.; Wilson, J. R.
Abstract: Many layered intrusions are considered to have been repeatedly inflated by magma additions, but rates of magma mixing relative to rates of layer accumulation are difficult to model. The nature of magma recharge through the interval including the Pyroxenite Marker (PM), Main Zone, Bushveld Complex, South Africa, is examined with regard to such processes. The plagioclase compositions (An value) in five previously published and three new profiles (presented here and focusing on the core compositions) that are at least 600 m in vertical extent and spread along a strike length of 110 km are evaluated. The compilation of the eight profiles shows the following trends. Upward reversals in compositions show considerable lateral as well as vertical variations. Lateral variations show a range in: (1) the minimum An value reached in each profile prior to the onset of magma recharge (An51 to An59 ); (2) the depth below the PM at which the minimum value is observed (50 to 575 m); (3) the An value close to the PM (An54 to An75 ); (4) the maximum value recorded above the PM (An63 to An76 ); (5) the height above the PM at which this maximum value is reached (0 to 300 m) – in all cases, the highest values of An occur at the northern end of the studied sections; and (6) the vertical extents over which the reversals occur range from 150 to over 600 m indicating very protracted magma additions and/or slow mixing. The PM terminates toward the south, and close to this termination the immediate footwall rocks to the PM change from north to south from gabbronorite to magnetite gabbronorite. A cross-section through these profiles defines two basins, with an intervening structural upwarp. The magma pulses that were added to produce very gradual and protracted reversals in mineral compositions through the PM interval ponded initially at the base of the northern basin, and did not homogenize the entire magma column. These added magmas did not overflow and have an effect on mineral compositions in the southern basin until after considerable replenishment and crystallization (including the PM) had taken place in the northern basin. We emphasize the prolonged period(s) of magma input and slow rate of vertical homogenization of the magma column during the formation of this sequence of as much as 400 m of the Main Zone.